Comunidades de relacionamento virtual como agentes potencializadores de emancipação - Beserra, Rael Bispo (2012)
The present research that works with the prospect of Social Psychology aims to understand the processes involving the metamorphosis of identity (CIAMPA, 1987, 1995) of people using the communities of virtual relationship as an important means of social constructions and their identity. The intensification of the virtual nowadays is an emerging issue that still generates some controversy as to the consequences for the individual and their socialization processes. It is likely and natural that differences remain for some time, we are facing a new reality. The research is just another contribution to other studies that certainly will happen. Virtual reality is becoming more real in people's life. This is a qualitative research technique that has as main, the Life History. This is a technique used in NEPIM (Center for Studies and Research in Identity-Metamorphosis), the program of Postgraduate Studies in Social Psychology from PUC-SP, coordinated by Prof. Drº Antonio da Costa Ciampa, with important results to Social Psychology. The research was based on a report of a person for about 12 years has systematic relationships with the same virtual community. The dissertation seeks to understand how a person uses virtual reality as potentiating agent of emancipation in their life trajectory. The critical and ethical position also allowed us to realize the risks of considering the realities - and virtual - disconnected, making clear the importance of understanding them as complementary and interdependent realities